Influence of Empathy Disposition and Risk Perception on the Psychological Impact of Lockdown During the Coronavirus Disease Pandemic Outbreak - Grignoli, Nicola; Petrocchi, Serena; Bernardi, Sheila; Massari, Ilaria; Traber, Rafael; Malacrida, Roberto; Gabutti, Luca (Frontiers in Public Health, 2021)
During the current COVID-19 pandemic, and especially in the absence of availability of an effective treatment or a vaccine, the main health measure is neither chemical nor biological, but behavioural. To reduce the exponential growth of infections due to the new coronavirus (SARS-CoV-2) and the resulting overburdening of the healthcare system, many European Countries, parts of the U.S., and Switzerland gradually implemented measures of quarantine and isolation defined as lockdown. This consideration leads to the need to understand how individuals are motivated to protect themselves and others. Recent research suggested that prosocial mental dispositions, such as empathy, might promote adherence to social norms of distancing. Other research conducted during the COVID-19 outbreak indicates, however, that empathy levels might fluctuate according to anxiety linked to the risk of death, and this negatively predicted prosocial willingness. The present protocol proposes a study on whether people's empathic dispositions, interacting with the levels of risk, influence the psychological impact of lockdown. The rationale is that emphatic dispositions, encouraging the acceptance of the lockdown, determine a better psychological adaptation and less distress. One retrospective study will be developed in Switzerland and, if the pandemic conditions force a new wave of lockdown on the population, one prospective study as well. A total of 120 participants will be involved, distinguished by their level of objective risk: 1) high objective risk (COVID-19 positive patients, hospitalized in isolation in post-acute phase); 2) moderate objective risk (COVID-19 positive patients, isolated at home); 3) minimum objective risk (non-positive adults, in lockdown). Measures of perceived risk of being contagious for third parties, empathic dispositions, and acceptance of lockdown will be collected. The expected results provide important answers related to the immediate impact of empathic dispositions, effective risk and risk perception on the psychological impact of lockdown during a pandemic outbreak. Data gathered from this study could inform policy makers and public health managers about the best communication strategies that will take into account the various stages of health risk and, in particular, to modulate messages to the population aimed at inducing self-isolation behavior